2013
DOI: 10.3390/catal3010148
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Polymerization Using (Imino)vanadium(V) Dichloride Complexes Containing (Anilido)methyl-pyridine, -quinoline Ligands–Halogenated Al Alkyls Catalyst Systems

Abstract: Abstract:The effect of ligand and Al cocatalysts in ethylene polymerization, using V(N-1-adamantyl)Cl 2 (L) [L = 2-(2,6-Me 2 C 6 H 3 )NCH 2 (C 9 H 6 N), 8-(2,6-Me 2 C 6 H 3 )NCH 2 (C 9 H 6 N)] and V(N-2-MeC 6 H 3 )Cl 2 [2-(2,6-R' 2 C 6 H 3 )NCH 2 (C 5 H 4 N)] (R' = Me, i Pr), has been explored. The reaction products in the presence of Et 2 AlCl or Me 2 AlCl cocatalyst were polyethylene whereas the reaction product of the 2-methylphenylimido analogues in the presence of MAO cocatalyst was 1-butene with high sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…are known to display uniquely high reactivity toward olefins in olefin coordination/insertion polymerization. The design and synthesis of efficient vanadium precatalysts for olefin coordination insertion polymerization has thus attracted considerable attention in the fields of catalysis, organometallic chemistry, and polymer chemistry. Our group has focused on (imido)­vanadium­(V) complexes containing anionic donor ligands of the type, VCl 2 (Y)­(NR) (Y = aryloxo, ketimide, phenoxyimine, etc. ), ,,, and has demonstrated that these complexes, exemplified by V­(N-2,6-Me 2 C 6 H 3 )­Cl 2 (O-2,6-Me 2 C 6 H 3 ) ( A in Scheme ), exhibit remarkable catalytic activities not only for ethylene polymerization but also for ethylene copolymerization with norbonene (NBE) in the presence of aluminum cocatalysts. Moreover, we also reported that (2-anilidomethyl)­pyridine-supported (imido)­vanadium­(V) complexes of the type, V­(NR′)­Cl 2 [2-ArNCH 2 (C 5 H 4 N)] [Ar = 2,6-Me 2 C 6 H 3 , etc. ; R′ = 1-adamantyl (Ad), cyclohexyl, o -tolyl, phenyl, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…are known to display uniquely high reactivity toward olefins in olefin coordination/insertion polymerization. The design and synthesis of efficient vanadium precatalysts for olefin coordination insertion polymerization has thus attracted considerable attention in the fields of catalysis, organometallic chemistry, and polymer chemistry. Our group has focused on (imido)­vanadium­(V) complexes containing anionic donor ligands of the type, VCl 2 (Y)­(NR) (Y = aryloxo, ketimide, phenoxyimine, etc. ), ,,, and has demonstrated that these complexes, exemplified by V­(N-2,6-Me 2 C 6 H 3 )­Cl 2 (O-2,6-Me 2 C 6 H 3 ) ( A in Scheme ), exhibit remarkable catalytic activities not only for ethylene polymerization but also for ethylene copolymerization with norbonene (NBE) in the presence of aluminum cocatalysts. Moreover, we also reported that (2-anilidomethyl)­pyridine-supported (imido)­vanadium­(V) complexes of the type, V­(NR′)­Cl 2 [2-ArNCH 2 (C 5 H 4 N)] [Ar = 2,6-Me 2 C 6 H 3 , etc. ; R′ = 1-adamantyl (Ad), cyclohexyl, o -tolyl, phenyl, etc.…”
Section: Introductionmentioning
confidence: 99%
“…; R′ = 1-adamantyl (Ad), cyclohexyl, o -tolyl, phenyl, etc. ], efficiently dimerize ethylene with both notable catalytic activity and high selectivity in the presence of methylaluminoxane (MAO), whereas the resulting products were polyethylene with ultrahigh molecular weight when the reactions were conducted in the presence of Et 2 AlCl or Me 2 AlCl. , …”
Section: Introductionmentioning
confidence: 99%
“…The activity of the catalyst system decreases with change of the Al/V molar ratio (higher or lower from the optimal value) (items 2, 3, 5, and 10, 11, 13), increase of reaction temperature up to 50 °C (items 8 and 16) or decrease of the monomer pressure (items 7 and 15). In contrast, increase of the monomer pressure (items 6 and 14) results in increase of the amount of polyethylene, which is related to better ethylene solubility . Prolonging the reaction time up to 1 h also has an advantageous effect.…”
Section: Resultsmentioning
confidence: 99%